Cognitive and imaging impacts of left ventricular hypertrophy in people with type 2 diabetes: Novel insights into the role of vascular risk factors in the development of Alzheimer's disease and neurodegeneration. (7th December 2020) - Restrepo, Carolina; Patel, Sheila; Werden, Emilio; Khlif, Mohamed Salah; Singleton, Rebecca; Bird, Laura J.; Ekinci, Elif; MacIsaac, Richard; Srivastava, Piyush; Burrell, Louise; Brodtmann, Amy
Abstract: Background: Older adults with type 2 diabetes mellitus (T2DM) are at an increased risk of cognitive decline and dementia. Left ventricular hypertrophy (LVH) is prevalent in T2DM and is independently associated with cognitive decline. We conducted a study to establish whether T2DM patients with LVH have increased rates of brain atrophy and cognitive impairment. Methods: Thirty‐seven cognitively healthy adults (50 years and older) with T2DM were divided into those with (n=13) and without (n=24) LVH. All participants completed neuropsychological assessments, health‐and‐lifestyle questionnaires, 24‐hour ambulatory blood pressure monitoring, an echocardiogram and a 3T‐MRI scan. FreeSurfer (version 6.0) was used to estimate total brain volume (TBV), mean cortical thickness and subcortical volumes, including the thalami and caudate nuclei. TBV was expressed as a percentage of intracranial volume. Averages between left and right volumes were calculated for subcortical structures. Left ventricular mass was indexed to height 2.7 using the American Society of Echocardiography criteria. LVH was defined as >49g/m 2.7 for males and >45g/m 2.7 for females. Three cognitive domains (visuospatial skills, verbal memory and executive functions) were derived through factor analysis. These variables were used to compare cognitive performance between individuals with and without LVH. Results: There was a higher percentage of women (x 2 =11.01, df=1, p <0.01) in the LVH group. No differences in cortical thickness and TBV were found between groups. The LVH group showed significantly lower volume in the cerebellar cortex (F(1, 32)=5.25 p=0.029) and in the amygdala (F(1, 32)=6.24 p=0.018) after correcting for sex, age, blood pressure and BMI when compared to the no LVH group. Significant differences were found in the visuospatial skills factor ( F (1, 43)=4.09; p = 0.049), with the LVH group performing worse than the no LVH group. Conclusions: The presence of LVH in individuals with T2DM was associated with atrophy in the cerebellar cortex and in the amygdala, as well as with poorer visuospatial function.